A Novel Approach to Measure Executive Functions in Students: An Evaluation of Two Child-Friendly Apps - Berg, Valeska; Rogers, Shane L.; McMahon, Mark; Garrett, Michael; Manley, Dominic (Frontiers in Psychology, 2020)
Interest in measurement of children’s executive functions has shown a major increase over the past two decades. The present study evaluates two new apps (EYT and eFun) for measuring executive functions in children. The results of this study show that children (aged 5-8) enjoy executive function assessment in the form of games on an iPad. However, only one executive function, EYT working memory, showed significant positive correlations with several types of grades (e.g., English and maths) in primary school students. New, self-assessed, child-friendly executive function measurement tools have the potential to provide future possibilities for teachers to integrate information on cognitive ability into student learning plans.